Addressing Gender Inequalities in Curriculum and Education : Review of Literature and Promising Practices to Inform Education Reform Initiatives in Thailand - Levtov, Ruti (World Bank, Washington, DC, 2014)
In Thailand and worldwide, despite increases in educational enrollment, rigid gender norms dictating appropriate roles and behaviors contribute to the persistence of the gender inequalities. Since education systems are embedded in the broader social context, they reflect the inequalities that exist in society. The structure and content of schooling, textbooks, curricular choices, sex distribution of teachers and administrators, teacher attitudes and behaviors, classroom and discipline practices, and the presence of violence, reflect discriminatory and harmful social norms about the appropriate roles and opportunities for boys and girls (Connell, 1996, 2000, 2010). At the same time, schools have enormous potential to effect social change, transform gender relations, expanding the range of possibilities for both boys and girls (UNGEI, 2012a). This report provides a brief review of the literature and of interventions to promote gender equity through education in several specific areas: textbooks and curriculum; teacher distribution, attitudes, and behaviors; and school violence and discipline. And the report looks at holistic interventions that address multiple dimensions. This review also gives an overview of important steps for assessing gender issues in the educational system, emphasizes the need for rigorous interventions that measure a broad range of outcomes, provides recommendations for policy and programming, and highlights tools and resources.